Tangible Tele-Meeting in Tangible Space Initiative - Lee, Joong-Jae; Lee, Hyun-Jin; Jeong, Mum-Ho; Jeong, SeongWon; You, Bum-Jae (SPRINGER SINGAPORE PTE LTD, 2014)
Tangible Space Initiative (TSI) is a new framework that can provide a more natural and intuitive Human Computer Interface for users. This is composed of three cooperative components: a Tangible Interface, Responsive Cyber Space, and Tangible Agent. In this paper we present a Tangible Tele-Meeting system in TSI, which allows people to communicate with each other without any spatial limitation. In addition, we introduce a method for registering a Tangible Avatar with a Tangible Agent. The suggested method is based on relative pose estimation between the user and the Tangible Agent. Experimental results show that the user can experience an interaction environment that is more natural and intelligent than that provided by conventional tele-meeting systems.
Keywords: VISION; TRACKING